THE IMPACT OF FAMILY PLANNING SERVICES BY THE JAMBI CITY POPULATION CONTROL AND FAMILY PLANNING OFFICE IN IMPROVING EDUCATION IN JAMBI CITY - Armand, Fadhilah Salsabilla; Setyowati, Endah; Sarwono, Sarwono (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Family Planning Services are a strategic effort in population control and the improvement of family education in Jambi City. In Jambi City, the Office of Population Control and Family Planning has implemented various services to generate positive impacts in support of family welfare. However, the concrete impact of these services on educational aspects still requires further research. This study aims to analyze the impact of Family Planning Services and their relationship to improving education in Jambi City. This research uses qualitative methods. It was found that the provision of Family Planning Services (KB) by the DPPKB in Jambi City can increase families' awareness and knowledge about the importance of participating in the KB program, enabling families to plan the number and spacing of their children's births, which positively affects the quality of children's education.